Structural and surface characterization of wide band gap semiconductors for high-speed transistor applications - Chen, Kai (Nanyang Technological University, 2020)
This report presents the research and characterization work during the final year project. The project focuses on the structural and electrical characterization of AlN/GaN/AlN (AGA) double-heterojunction high electron mobility (HEMT) heterostructures on SiC substrates, and simulation of AGA HEMTs as well as InAlGaN/GaN quaternary HEMTs. The simulation study was carried out by using the self-consistent 1D Schrodinger-Poisson program. The main aim of this work is to build material parameters of InxAlyGa1-x-yN barrier layer from the known binary nitrides and study two dimensional electron gas (2DEG) density as a function of InxAlyGa1-x-yN barrier thickness for InAlGaN/GaN based high electron mobility transistors (HEMTs). It was observed that the 2DEG density increases with increasing InAlGaN thickness. A sheet carrier density of 1.215×1013 cm-2 for a 10 nm quaternary barrier and 500 nm GaN was simulated, which is slightly lower than the reported results, indicating further optimization of the material database is required. Simulation studies were also conducted on AGA structures. The 2DEG density as a function of GaN channel and AlN barrier layer thicknesses for the different surface potential of GaN was studied. AlN barrier layer thickness was found to have a higher impact than GaN channel thickness on the 2DEG density. Further, lower surface potential resulted in higher 2DEG concentration. In addition to simulations, Characterization of AlN/GaN/AlN HEMTs was carried out, and, growth samples were analyzed by optical microscopy, atomic force microscopy, and Hall measurement system. Data from high-resolution X-ray diffraction was measured by the staff in the lab and analysed with help from the team. Smooth and crack-free surface of both AlN and GaN layers in AGA structures were characterized. The completed AGA structure show that 2DEG is developed at AlN/GaN heterointerface. As predicted in simulations, 2DEG density increased with increased barrier layer thickness. An optimized AGA structure with 2DEG density of 3.86 ×1013 cm-2 and with carrier mobility of 629 cm2/V.s was achieved. Matching of experimentally obtained 2DEG density values with simulated results showed that MBE grown AGA structures has a surface potential of 0.8 eV.